Metaphoric interventions for challenging irrational thoughts and attitudes in substance use disorders - Hosnia Shehata Mohamed; Manal Abo Elial Abo elkiat Hamad; Gellan K. Ahmed; Shymaa Mohammed Sayed Hassan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Substance use disorders are often accompanied by irrational beliefs and unfavorable attitudes that contribute to their development and persistence. Metaphor therapy, utilizing stories and imagery, has emerged as a potential intervention to reshape thoughts. This study aimed to investigate the impact of metaphor therapy on irrational beliefs and attitudes among individuals with substance use disorders. A quasi-experimental study was conducted at Assiut University Hospital’s substance use inpatient unit from April to December 2023. A non-probability purposive sample of 115 individuals with substance use disorders was selected but only 100 were recruited and randomly assigned to study and control groups. The study group (n = 50) received six 90-min group metaphor therapy sessions over 6 months, while the control group (n = 50) received no intervention. Irrational beliefs and attitudes toward substance use were assessed using the Irrational Beliefs Scale and Attitude Toward Substance Abuse Questionnaire at pre-treatment, post-treatment, and follow-up. Results The metaphor therapy group demonstrated significant decreases in mean irrational belief subscale and total scores at post-treatment and follow-up compared to pre-treatment. Additionally, this group exhibited higher mean attitude scores, indicating more negative attitudes (rejection of substance use) during post-treatment and follow-up assessments. No significant changes were observed in the control group. Conclusions Metaphor therapy was effective in reducing irrational beliefs and fostering more favorable attitudes toward substance use among individuals with substance use disorders. The finding suggests metaphor therapy could be a valuable intervention for addressing cognitive and attitudinal factors contributing to substance use.